The Use of Community Based Participatory Research to Assess Perceived Health Status and Health Education Needs of Persons in Rural and Urban Haiti - Debra Pettit Whisenant; Cyndi Cortes; Patrick Ewell; Norma Cuellar (Rural Nurse Organization; Binghamton University, 2017)
PURPOSE: Haitian communities have limited access to health care. The purpose of this study was to determine the perceived self-health status and health education needs of rural versus urban Haitians using a Community Based Participatory Research design. SAMPLE: Residents of two rural and one urban Haitian communities (n = 340) were surveyed to obtain demographic information, perceived health status, and priority of health education topics. METHOD: Surveys were used to collect demographic data and the personal importance of various health education topics were obtained. Native Haitians were trained to use the survey instrument and conducted the short interview with willing participants in rural and urban settings. FINDINGS: Health related status significantly varied by rural versus urban community type in that those in urban communities (M = 2.64, SD = 1.10) viewed their health as significantly better than those in rural communities (M = 2.26, SD = 1.14), t(324) = 2.93, p = .004. The highest rate topics for requests in health education included spiritual health (M = 4.44, SD = 0.84). Interest was shown in learning about injury prevention, improving maternal mortality, helping children live longer, environmental issues such as water, food, and sanitation. Less interest was shown in learning about weight management and exercise. CONCLUSIONS: A health education curriculum was developed to train laity in faith based organizations to be community health promoters. This project offers sustainable interventions to empower communities to take responsibility of their own health. DOI:  http://dx.doi.org/10.14574/ojrnhc.v17i1.427